PERENCANAAN INSTALASI PENERANGAN PADA KAPAL ISAP PRODUKSI PT. TIMAH (PERSERO) TBK - Riswan Ifria; Ilham Gantar Friansyah; Edikurniawan (Fakultas Sains dan Teknologi Universitas Karimun, 2020)
On the suction ship produced by PT. Timah (Persero) Tbk applies a lighting system using standards from the 2012 Minister of Health Decree regarding the level of lighting in the work environment. With this standard, it is expected that each manganese lighting will function properly according to the active needs of the task. The lamp used for lighting in each room is Philips TL-D 36 Watt with Pacific TCW097 type, so the lamp can last a long time because it is protected from dust which can reduce the quality of the lamp. The results of research on the use of energy, in this case electricity in shipping plays a very important role for the needs of manganese lighting. Therefore the lighting system of a room on the ship must be planned well taking into account the energy conservation efforts that can be done